2010
DOI: 10.1007/s11739-010-0361-1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers and coronary heart disease: from bench to bedside and back

Abstract: Inflammation plays a pivotal role in all stages of atherosclerosis from endothelial dysfunction and plaque formation to plaque destabilization and disruption. Inflammatory biomarkers, originally studied to better understand the pathophysiology of atherosclerosis, have generated increasing interest among clinicians, because of their utility in the challenging problems of diagnosis and risk assessment of patients with suspected or proved coronary heart disease. Moreover, in fascinating perspective, they could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 52 publications
1
25
0
1
Order By: Relevance
“…Several subsequent prospective studies have consistently shown that baseline IL-6 levels are powerful predictor of cardiovascular events in apparently healthy subjects [69]. In the Framingham Heart Study patients without history of AMI or HF but with elevated IL-6, TNF-alpha and CRP levels had a markedly increased risk of developing HF.…”
Section: Interleukinesmentioning
confidence: 98%
See 1 more Smart Citation
“…Several subsequent prospective studies have consistently shown that baseline IL-6 levels are powerful predictor of cardiovascular events in apparently healthy subjects [69]. In the Framingham Heart Study patients without history of AMI or HF but with elevated IL-6, TNF-alpha and CRP levels had a markedly increased risk of developing HF.…”
Section: Interleukinesmentioning
confidence: 98%
“…More than 40 prospective studies among apparently healthy individuals have demonstrated that baseline CRP level is an independent predictor of future cardiovascular events, even beyond the Framingham risk score, and that it determines an improvement of the net reclassification index [15,69,83,84]. These studies included both men and women, European and American populations and both middle-aged and elderly patients.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
“…Inflammatory processes play a pivotal role in all stages of the development of both acute and chronic atherosclerosis, from the initial induction of endothelial dysfunction and plaque formation to plaque destabilization and disruption with superimposed thrombosis leading to acute MI or death (Biasillo et al 2010). During the entire process there is a contribution of activated inflammatory cells as neutrophils, lymphocytes, monocytes and resident macrophages, which are secreting pro-inflammatory cytokines.…”
Section: Clinical Cardiovascular Diseases Inflammation and Ykl-40mentioning
confidence: 99%
“…Представляются важными и данные о том, что повышенная экспрессия медиаторов воспаления (ФНО-α, ИЛ-1β, ИЛ-6, молекулы адгезии) наблюдается не только в крови, но и в миокарде [18,19,28]. Уси-ленная миокардиальная экспрессия цитокинов, обна-руживаемая при дисфункции миокарда, предполага-ет центральную роль цитокинов в развитии процессов ремоделирования миокарда и возникновении ХСН.…”
Section: Discussionunclassified